ANALISIS FAKTOR YANG MEMPENGARUHI INVESTASI DI INDONESIA - Ridwan Firadlan (2021)
Investment has an important role in the Indonesian economy, it can be said to be an engine that drives economic development. First, investment encourages national income (economic growth) is multiplied through the process of multiplier. Second, investment will encourage job creation, reduce unemployment, reduce poverty and overcome other associated problems. Third, investment can also be used as a means of equity, both between sectors and between individuals. This study aims to analyze the factors that influence investment in Indonesia in 1990-2019 with the variables of inflation, interest rates, exchange rates and labor. This type of research uses quantitative, the type of data uses secondary data and the data used is the 1990-2019 time series. The method used in this study is a multiple linear regression analysis model using the OLS method. The results of multiple regression analysis show that (1) there is a significant effect of inflation on Indonesian investment (2) interest rates have a significant effect on Indonesian investment (3) Exchange rates have a significant effect on Indonesian investment (4) labor has a significant effect on Indonesian investment.